Management Perawatan Luka Herpes Pada Anak Usia Toodler - Anamuddin Pratama, Fahri; , Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
Background: Herpes Zoster (HZ) is one of the skin diseases caused by viral infection, which is due to virus reactivationVaricella-zoster (VZV). Most viral infections are mild and self-limiting, but HZ can lead to persistent pain complaints or postpetic herpetic neuralgia (NPH) that can lead to a decline in quality of life. Herpes Zoster in children attacks the lower cervical area, The high infection in Indonesia 2/3 of the 15-year-old population is seropositive to antibodies. The impact of herpes on children if not treated will result in damage to skin integrity in children, tissue damage, and disability. Objective: management of herpes zoster problems in children in accordance with nursing care is with wounding perewatan. Method: The method used is descriptive in toodler child with case study approach that is doing nursing asuahn starting from assessment, intervention, implementation, and evaluation which done in health center. Result: after done nursing care for 3 days home visit got diagnoses that appear on toodler child that is Degradation of skin integrity related to disease process. Conclusion: nursing problems that occur in children toodler partially resolved.